Application Of Apis dorsata Binghami Bee Nest Extract On The Effects Of Human Blood Lipid Reduction - Dina Munawaroh; Yermia S Mokosuli; Anita C. C. Tengker (Universitas Negeri Manado, 2021)
Honey, royal jelly, bee pollen, bee wax, propolis, bee glue, and bee venom/ apitoxin are among the items produced by honey bees. Honey, pollen, bees, eggs, larvae, and pupae are all stored in the A. dorsata Binghami beehive. Secondary metabolites and bioactive phenolic compounds (phenols, phenolic acids, esters, flavors, dihydroflavones, flavanols, chalcones, and phenolic glycerides), essential oils (mono and sesquiterpenes), polysaccharides, amino acids, amines, lactones, quinones, steroids, and vitamins) can all be found in honeycomb. The goal of this study is to see how A. dorsata Binghami honeycomb tea affects blood lipid levels in humans after 14 days of consumption in a small group of male and female volunteers who were given a 2 gram tea bag extract of A. dorsata Binghami honeycomb simplicia to drink once a day to see how it affects lipid levels (total cholesterol, LDL, HDL, and TAG) in human blood. Total cholesterol (140.56 mg/dL), triglycerides (140.93 mg/dL), LDL (85.92 mg/dL), and HDL (21.49 mg/dL) were all found to be high in humans. As a result,